Effect of Activation Time on the Quality of Microwave-Activated Sago Trunk Charcoal Briquettes (Metroxylon Sagu Rottb) - L. Lestari; I. N. Sudiana; S. Raharjo; L. O. M. Salam; I. W. Sutapa (International Journal of Acta Material, 2024)
Research has been conducted on the effect of activation time on the quality of sago stem charcoal briquettes (Metroxylon Sago Rottb) activated by microwave. This experimental study aimed to determine the impact of activation time on various parameters of sagu stem charcoal briquettes, including density, moisture content, ash content, volatile matter content, fixed carbon content, calorific value, and combustion characteristics such as ignition time and flame rate. The research involved several stages, including raw material collection, carbonization, grinding and sieving, adhesive mixing, printing and bulking, drying, and quality assessment of the briquettes. Sago stem charcoal briquettes were produced using sago as an adhesive at a ratio of 9:1. The charcoal powder was sieved using an 80-mesh sieve. The samples were printed and compacted at a pressure of 100 kg/cm2 and activated using a 150-watt microwave for durations of 5, 6, and 7 minutes. The results demonstrated that the density ranged from 0.3601 to 0.4892 g/cm3, moisture content ranged from 2.103% to 3.369%, ash content ranged from 4.6422% to 6.4706%, volatile matter content ranged from 80.306% to 84.740%, fixed carbon content ranged from 7.222% to 11.1205%, calorific value ranged from 5467.5 cal/g to 5805.5 cal/g. The briquettes activated by microwave, under a pressure of 100 kg/cm2, exhibited the highest quality, with a combustion rate ranging from 0.0137 g/min to 0.0183 g/min, maximum temperature ranging from 519 oC to 538 oC, and a briquette flame duration ranging from 29 minutes to 35 minutes.